Chapter 16. Strawberry Production - Vance M. Whitaker; Nathan S. Boyd; Natalia A. Peres; Johan Desaeger; Sriyanka Lahiri; Shinsuke Agehara (EDIS, 2021)
Chapter 16 of the Vegetable Production Handbook.